2016
DOI: 10.1159/000446992
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effectiveness of Intravitreal Ranibizumab for Diabetic Macular Edema in Vitrectomized and Nonvitrectomized Eyes

Abstract: Purpose: To compare the effectiveness of intravitreal ranibizumab (IVR) for diabetic macular edema (DME) between eyes with and without previous vitrectomy. Procedures: We prospectively assessed the best-corrected visual acuity (BCVA) and central macular thickness (CMT) after IVR for 6 months. Results: There were no significant differences in the baseline BCVA and CMT between both groups. In the nonvitrectomized group (n = 15), the mean changes of BCVA and CMT from baseline to month 6 were significant (p < 0.01… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…Chen et al [3] reported that the number of IVR injections was significantly less in nonvitrectomized than in vitrectomized eyes (4.1±0.6 vs. 5.1±0.7, respectively; p<0.001) during a 6-month period. In the study by Koyanagi et al [4], the number of IVR injections during the 6-month period was similar in both nonvitrectomized and vitrectomized eyes (4.5±1.2 vs. 4.9±1.3, respectively; p=0.484). In our study, the number of IVR injections until month 6 was significantly higher in nonvitrectomized eyes than vitrectomized eyes (3.2 vs. 1.3, respectively; p=0.04), which was probably due to the loading dose applied to the nonvitrectomized eyes in the first three months.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Chen et al [3] reported that the number of IVR injections was significantly less in nonvitrectomized than in vitrectomized eyes (4.1±0.6 vs. 5.1±0.7, respectively; p<0.001) during a 6-month period. In the study by Koyanagi et al [4], the number of IVR injections during the 6-month period was similar in both nonvitrectomized and vitrectomized eyes (4.5±1.2 vs. 4.9±1.3, respectively; p=0.484). In our study, the number of IVR injections until month 6 was significantly higher in nonvitrectomized eyes than vitrectomized eyes (3.2 vs. 1.3, respectively; p=0.04), which was probably due to the loading dose applied to the nonvitrectomized eyes in the first three months.…”
Section: Discussionmentioning
confidence: 80%
“…They reported significantly improved BCVA and central foveal thickness in nonvitrectomized eyes than in vitrectomized eyes. [3] Koyanagi et al [4] compared the efficacy of IVR in 10 vitrectomized and 15 nonvitrectomized eyes and reported no significant differences in the mean changes of BCVA and CMT between both groups at 6 months. Our short-term (6-month) findings in favor of nonvitrectomized eyes were in line with these reports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This indicated that eyes with previous vitrectomy tended to show less improvement in visual acuity and that eyes with previous PRP or the disruption or disappearance of the ELM tended to show more improvement in visual acuity. Our previous studies suggested that an antiangiogenic shift occurs in the vitreous after vitrectomy and that the improvement is slower after intravitreal ranibizumab in patients with vitrectomized eyes [25,26]. This, in turn, would be expected to lead to a positive correlation with ΔBCVA M12 .…”
Section: Discussionmentioning
confidence: 96%